Estacionalidad de la coccidiosis del ternero - Rodriguez, N.=700 1 Moreno, A.; Fustes, B.; Gonzalez, R.; Percedo, M.I.
(Es, En)
Ilus., 9 ref.
Keywords: TERNERO; EIMERIA; COCCIDIOSIS; ESTACIONES DEL AÑO; PERIODICIDAD; CUBA